Kahverengi Mercimek Nişastasının Karakterizasyonu Ve Lipidler İle Dirençli Nişasta Tip 5 Oluşturma Özelliklerinin İncelenmesi - Okumuş, Bahar Nur (Fen Bilimleri Enstitüsü, 2015)
Baklagiller, insanlar tarafından ilk olarak 3000 yıl önce yetiştirilen Leguminosae ailesine aittir. Bu ailenin bireyleri, mükemmel bir karbonhidrat (%50-60) ve ucuz protein kaynağı (%20-24) olmaları sebebiyle dünyada tahıl ürünlerinden sonra en önemli ikinci gıda kaynağıdır.  Mercimek, FAO’nun belirlediği 11 en yaygın tüketilen bakliyat çeşitleri arasında 7. sırada yer almaktadır. Mercimek (Lens culinaris) mercek-şekilli tohumlara sahip baklagil türüdür. Sarı, yeşil, kırmızı, kahverengi ve siyah gibi farklı renklerle geniş bir yelpazaye sahiptir. Yüksek protein içeriğinin yanı sıra, mercimekte diyet lifi, folat, manganez, fosfor ve B1 vitamini içeriği de oldukça yüksektir. Hastalıklara dayanıklı çeşitlerin ıslahı ve bunların kullanılması ile makineli hasada geçilmesi dünya mercimek veriminin son 40 yılda %102,9 oranında artış göstermesini sağlamıştır. Ülke bazında dünya mercimek verimine bakıldığında Türkiye 3. sırada yer almaktadır. Kahverengi mercimek, Türkiye’de Malatya bölgesine özgü bir mercimek çeşididir ve Lens culinaris Medikus ailesine dahildir. Yeşil mercimek türüne göre daha küçük boyutta ve daha yuvarlak şekle sahiptir.  Bu çalışmada kullanılan kahverengi mercimek, Duru Bulgur firmasından temin edilmiştir. Kahverengi mercimek nişastasını ve mercimeğin öğütülmesiyle elde edilen kahverengi mercimek ununu tanımlamak amacıyla komposizyon analizleri uygulanmıştır. Nişasta ve una ait elde edilen nem içeriği değerleri sırasıyla %14,5 ve %12,9; kül içeriği değerleri %0,3 ve %2,9; protein içeriği değerleri %0,8 ve %24,9; yağ içeriği değerleri %0,4 ve %2,5 olarak bulunmuştur. Kahverengi mercimeğin amiloz/amilopektin oranı ise 29:71 olarak tespit edilmiştir. Amiloz-lipid kompleksi, enzim hidrolizine direnci sebebiyle DN tip 5 olarak tanımlanmıştır. Nişasta granüllerinde amiloz-lipid komplekslerinin oluşması, pişirme sırasında granüllerin şişmesini kısıtlayarak nişastanın enzime direncini arttırmaktadır. Amiloz-lipid komplekslerinin enzime dirençleri lipidlerin moleküler yapısına ve tekli sarmalların kristal yapısına bağlıdır. DN Tip 5 diyeti ile tokluk glisemik ve insülinemik indekslerinde azalma rapor edilmesi, DN Tip 5’i tip-2 diyabet, obezite, hipertansiyon, kalp rahatsızlıkları gibi metabolik sendromlar için önerilen diyet yapmaktadır.  Bu çalışmada; amiloz-lipid kompleksi oluşturulma özelliklerini incelemek üzere mısır yağı, zeytin yağı, soya yağı, hidrojenize ayçiçek yağı, palmitik asit ve stearik asit kullanılmıştır. Amiloz-lipid komplekslerinde ilk aşamada dirençli nişasta tayini, hızlı sindirilen nişasta tayini ve yavaş sindirilen nişasta tayini gerçekleştirilmiştir. Kahverengi mercimek nişastasının %9,9 olarak bulunan dirençli nişasta içeriğinin yağ veya yağ asidi ilavesiyle önemli oranda arttığı (%1,9-5,0) gözlemlenmiştir. Lipid ilaveli nişastaların dirençli nişasta içeriği ile lipid ilaveli pişirilmiş nişastalarınki karşılaştırıldığında, pişirme işleminin dirençli nişasta içeriğinin %2 oranında artmasında etkili olduğu görülmüştür. Doğal nişasta ve %10 lipid ilaveli pişirilmemiş ve pişirilmiş nişasta örneklerinin termal özellikleri diferansiyel taramalı kalorimetre (DSC) ile incelenmiştir. Buna göre jelatinizasyon pik değerleri (Tp) ve entalpi değerleri karşılaştırıldığında lipid ilaveli örnekler ile saf kahverengi mercimek nişastası arasında önemli bir fark gözlenmemiştir. Ancak amiloz-lipid kompleksine ait geçişin entalpisi en yüksek hidrojenize ayçiçek yağı ilave edilen örnekte gözlenmiştir. Taramalı Elektron Mikroskobu (SEM) kullanılarak kahverengi mercimek ununun, saf kahverengi mercimek nişastasının ve %10 lipid ilaveli pişirilmemiş ve pişirilmiş nişasta örneklerinin granül yapıları ve dağılımları incelenmiştir. Saf kahverengi mercimek nişastasının oval granüller halinde olduğu, un yapısının ise nişasta granüllerine bağlı olan protein molekülleri ile daha kompleks bir yapıda olduğu görülmüştür. Lipid ilaveli nişasta örneklerine ait görüntülerde nişasta sarmalının içindeki boşluğa özellikle doymuş yağ asitleri içeren yağ veya doymuş yağ asitlerinin yerleştiğini gösteren beyaz renkli granüllerin görüntüleri elde edilmiştir. Pişirilmiş nişasta örneklerine ait görüntüler incelendiğinde ise granüller yapının pişirme işlemi sebebiyle bozulduğu, ancak kristal yapının daha belirgin olduğu görülmüştür.  Farklı yağların (mısır yağı, soya yağı, zeytin yağı, hidrojenize ayçiçek yağı) ve yağ asitlerinin (palmitik asit, stearik asit) nişastanın sindirilebilirliği, amiloz-lipid kompleksi oluşumu ve termal özellikleri üzerine farklı etkileri gözlenmiştir. Nişasta ve lipidlerin birbiriyle olan etkileşimi düşük glisemik indekse sahip nişastalı gıda formülasyonlarının geliştirilmesinde faydalı olacağı düşünülmektedir. Yağların farklı kaynaklardan elde edilen nişastalarla etkileşimlerinin inceleneceği yeni çalışmalara ihtiyaç olduğu görülmektedir.

Pulses were cultivated by humans 3000 years ago and belong to the family Leguminosae. Members of the family are the second most important food source in the world after cereal grains as they are excellent source of carbohydrates (50-60%) and an inexpensive source of proteins (20-24%). Pulses are recommended as a staple food by health organizations due to their rich sources of vitamins, minerals and carbohydrates in the human diet. In addition, they have important role for being source of protein to vegetarians. FAO recognizes 11 primary pulses and lentil is the 7th of this list. The lentil (Lens culinaris) is a feathery legume with lens-shaped seeds. Lentil types comprise a wide variety with that colors that include yellow, red, green, brown and black. In addition to the high protein content, lentils are high in dietary fiber, folate, manganese, phosphorous and B1. The improvement of disease resistant cultivars and the use of harvesting machine have increased the yield of lentil production as 102,9% for the last 40 years worldwide.   Turkey takes 3rd place when all countries are considered regarding lentil production yield. Brown lentil is special to Malatya region and belongs to Lens culinaris Medikus. It is smaller in size with respect to green lentil and have ball-like structure. Starch is the major carbohydrate source in human diet and it consists of amylose and amylopectin. Amylose is an essentially linear molecule with -1,4 linkages, whereas amylopectin is a highly branched with -1,6 linkages. Starch has commercial importance for food industry due to its desirable functional properties. One of the important properties of starch is its ability to absorb water which results in gelatinization and loss of granular organization. Legume starches are characterized by their high amylose content (25-65%). The high amylose content is responsible for a higher resistant starch content which results in their lower digestibility. Due to important nutritional characteristic of legume starches, their value in the industry is increased especially for chronic diseases such as obesity, cardiovascular disease and colon cancer.  As a major energy source, starch is hydrolyzed to glucose by amylolytic enzymes which is present in the gastrointestinal tract. Glucose is then absorbed in the small intestine and increases the blood glucose concentration. However, it has been realized that starch is not completely digested in the small intestine. Most starch products contain rapidly digestible starch (RDS), slowly digestible starch (SDS) and resistant starch (RS). Resistant starch is classified into four groups: RS1, RS2, RS3 and RS4. RS1 is physically inaccessible starch. RS2 is partialyy crystalline native uncooked starch granules. RS3 is especially formed in cooked products such as breads, corn flakes or potatoes after cooling and it consists of retrograded amylose. RS4 can be produced by chemical modifications (conversion or cross-linking). Because of the growing population suffering with insulin resistance, diabetes, overweight, obesity, and other related metabolic syndromes, there are increasing demands for starchy foods that have reduced glycemic-index. Amylose-lipid complex has been proposed as RS type 5 due to its resistance to enzyme hydrolysis. Molecular structures of the complexing lipid & amylose and the crystalline structure of the amylose-lipid complex affect the enzyme resistance of amylose-lipid complex. Amylose-lipid complex is generally found in native starch and processed starch. The hydrocarbon chain of the lipid interacts with the hydrophobic moiety of the amylose chain and fills the central cavity of the amylose single helix. The presence of amylose-lipid complex in starch granules increases their enzyme resistance by restricting the granule swelling during cooking. The enzyme resistance of amylose-lipid complex depends on the molecular structure of the lipid and the crystalline structure of the single helices. As it is reported that the diet with RS type 5 reduced postprandial glycemic and insulinemic responses, RS Type 5 is suggested as a potential to intervene in metabolic syndromes inclusing type-2 diabetes, obesity, hypertension, and heart disease. Compared with control bread made with wheat flour, ingestion of bread with palmitic acid-complexed RS5 causes less postprandial plasma-glucose and insulin responses. Composition analyses are done to define brown lentil used in this study is obtained from Duru Bulgur company. Brown lentil starch and brown lentil flour. Moisture content of 14,5% and 12,9%; ash content of 0,3% and 2,9%; protein content of 0,8% and 24,9%; fat content of 0,4% and 2,5% were obtained for the starch and flour, respectively. Amylose/amylopectin ratio is determined as 29:71 for brown lentil starch. Corn oil, olive oil, soy oil, hydrogenated sunflower oil, palmitic acid and stearic acid are used to form amylose-lipid complex. As a first step, resistant starch analysis, rapidly digestible starch analysis and slowly digestible starch analysis were done on amylose-lipid complexes. Resistant starch content of brown lentil starch was calculated as 9,9% which was increased by addition of lipid or fatty acids (1,9-5,0%). When the resistant starch content of lipid added starch samples and lipid added cooked starch samples were compared, it is seen that cooking has an effect on 2% increase of resistant starch content. Thermal properties of native starch and 10% lipid added uncooked and cooked starch samples were obtained by differential scanning calorimetry (DSC). According to this, there is no difference for gelatinization peak temperatures (Tp) and enthalpy values of lipid added starch samples and native brown lentil starch. On the other hand, amylose-lipid complex transition entalpy was found to be higher in hydrogenized sunflower oil. Scanning electron microscope (SEM) was used to obtain the granular structure and distribution of native brown lentil starch, %10 lipid added uncooked and cooked starch samples. It is observed that brown lentil starch has oval granular shape while  brown lentil flour has more complex structure with protein molecules embedded into starch granules. Opaque white granule structures were observed for saturated fatty acids or lipids that are added to starch samples, which is indicating that lipids and fatty acids interacting with the amylose chain and fills the central cavity of the amylose single helix. The images of cooked starch samples show that granuler structure of starch were lost and crystal structure became more distinct because of the cooking and cooling process. Rapid visco analyzer (RVA) measurements show that the addition of fats and fatty acids result in decrease of peak viscosity. Palmitic acid and stearic acid added starch samples show the lowest peak viscosity values as 1468 cP and 1366,5 cP respectively. It was observed that different lipid types (corn oil, soy oil, olive oil, hydrogenated sunflower oil) and fatty acids (palmitic acid, stearic acid) had different effects on digestibility, amylose-lipid complex formation and thermal properties of starch. By this konwledge gained from this study, new starch and lipid containing formulations having reduced glycemic index can be developed. Future studies are also necessary to investigate the effects of lipids with different starches derived from various sources.
Characterization Of Brown Lentil Starch And Investigation Of Resistant Starch Type V Formation With Different Lipids
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Nişasta; Dirençli Nişasta; Amiloz Lipid Kompleksi; Starch; Resistant Starch; Amylose Lipid Complex